"Polskie miesiące": sierpień [blok znaczków podziemnych] . "Polish months": August. Sheet of unofficial stamps - Victor. (Poczta Solidarność, 1985)
Brown and red print on white paper, without perforation. Sheet, with "Poczta Solidarność" imprint, part of the "Polish Months" series, consists of 3 stamps which represents events in Polish history that happened in August: the Polish-Soviet War (1920), Warsaw Uprising (1944) and August Accords (1980). Price range: 30-40 zł per stamp.